2017
DOI: 10.15446/rfna.v70n1.61768
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin resistant Staphylococcus aureus isolated from meat raw in Cartagena, Colombia

Abstract: To determine the prevalence of Methicillin Resistant Staphylococcus aureus (MRSA) isolated in establishments that commercialize raw ground beef and pork chops in Cartagena- Colombia. 160 samples were analyzed through microbiological cultures in Baire Parcker agar, and it was determined the presence of mecA gen that codifies the methicillin resistance and the pvl that codifies the Panton- Valentine leukocidin toxin (PVL) by the multiplex PCR technique. The antibiotic susceptibility profile for MRSA strains was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…Notably, 82% of isolates were found to be MRSA and it is slightly lower than the results of a study reported from Jimma, Ethiopia (90%) [46], on the other hand, much higher than the values observed in a study from Colombia (7.5%) [61]. The presence of MRSA isolates in meat samples hints at a fast-growing and risky situation directly affecting the public health system and the community [10].…”
Section: Plos Onecontrasting
confidence: 58%
“…Notably, 82% of isolates were found to be MRSA and it is slightly lower than the results of a study reported from Jimma, Ethiopia (90%) [46], on the other hand, much higher than the values observed in a study from Colombia (7.5%) [61]. The presence of MRSA isolates in meat samples hints at a fast-growing and risky situation directly affecting the public health system and the community [10].…”
Section: Plos Onecontrasting
confidence: 58%
“…In June 2002, the first clinical isolate of S. aureus completely resistant to vancomycin was isolated from a patient in the United States (CDC, 2002). Some other workers (Gutierrez et al, 2017) did not observe S. aureus resistance to vancomycin in poultry meat samples. Otalu et al (2011), reported that 100% S. aureus isolates from poultry meat were resistant to tetracycline and 61.5% resistant to methicillin in Nigeria.…”
Section: Discussionmentioning
confidence: 88%
“…The use of antibiotics in human hospitals and for animal production may result in the increased occurrence of bacterial resistance (Akbar & Anal, 2013). Antibiotics are also used as antimicrobial growth promoters in animal production (Gutierrez et al, 2017), especially in poultry production. In Nigeria, there is widespread misuse/abuse of antibiotics, particularly in poultry production.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies, S. aureus at contamination levels of 5 log CFU/100 cm 2 -7 log CFU/100 cm 2 was detected on dry stainless steel surfaces for at least 96 h. Even at a low contamination level of 3 log CFU/100 cm 2 , S. aureus can still be found within 48 h [70]. In a study in Colombia, Gutierrez et al [71] found MRSA in three pork processing facilities and two institutional kitchens. Methicillin-resistant S. aureus was not found in the nose and hands of humans, but there were 31 people (33%) who carried methicillin-sensitive S. aureus (MSSA).…”
Section: Transmission Of Mrsa On Pork and Pork Productsmentioning
confidence: 98%
“…The second case was food poisoning caused by pork contaminated with the toxin-producing strain of MRSA [46]. Investigations among professional pork handlers in the Netherlands revealed that even high-frequency exposure to MRSA resulted in a low MRSA colonization rate of ≤3% [71]. Pork and pork products contaminated with MRSA can be a source of LA-MRSA transmission to the community, but this is avoidable by following standard recommendations for hygienic handling and adequate heating of pork and pork products.…”
Section: Public Health Importancementioning
confidence: 99%